The impact of a single bout of high-intensity interval exercise on executive function in adolescents and young adults: A systematic review and meta-analysis - Zhang, Mufan; Zou, Yuping; Liu, Yongsen; Yang, Yi; Zhang, Tingran; Luo, Jiong (Pedagogy and Psychology of Sport, 2026)
Objective: Cognitive function is a critical developmental indicator in adolescents and young adults, and physical activity has been shown to enhance cognitive abilities. However, the effects of high-intensity interval exercise on cognitive function in adolescents and young adults remain unclear. Methods: A literature review was conducted, with systematic searches across three databases. Two researchers independently screened the studies based on inclusion criteria, assessed the risk of bias, and, following the organization of relevant literature, performed a Meta-analysis using RevMan 5.4 software. Results: Based on 13 studies involving 559 adolescents, the meta-analysis revealed distinct outcomes depending on the study design. In single-arm studies, acute high-intensity interval exercise significantly improved Stroop Task reaction time (WMD = -1.47, P < 0.00001), with subgroup analyses suggesting that cycling interventions lasting 30 minutes were most effective. However, these studies also showed a significant decrease in the number of correct responses (P = 0.0003). In contrast, randomized controlled trials (RCTs) observed no significant improvement in reaction time (P = 0.62). Conclusion: High-intensity interval exercise interventions in adolescents and young adults were associated with enhanced reaction speed and information processing capacity; however, no improvements have been observed in accuracy. The effects on cognitive control require further investigation.